Detecting changes in the heart rate of firefighters to prevent smoke inhalation and health effects - Sebastião, Raquel (2021)
Firefighters can suffer serious health problems and experience cardiac disorders derived from high pollutants inhalation. During experimental field burns, environmental and heart rate data from firefighters were collected and it was possible to observe that changes in heart rate were related with variations in pollutants inhalation. Therefore, detecting changes in heart rate may provide a good indicator to identify hazardous situations for firefighters. An automated method, based on the detection of changes in the heart rate, is proposed to prevent and to avoid serious undesirable side-effects in the health of firefighters due to pollutants inhalation. Within the experiments performed, a precision and a recall of 91.5 and 78.2%, respectively, were obtained. Furthermore, this approach can be part of a real-time decision support system for routine use in firefighting practice. Our results show the potential to provide effective support in real operational scenarios and that further research on the impact of environmental conditions in the well-being of firefighters is of utmost importance.